2018
DOI: 10.3389/fimmu.2018.00867
|View full text |Cite
|
Sign up to set email alerts
|

IRF3 Negatively Regulates Toll-Like Receptor-Mediated NF-κB Signaling by Targeting TRIF for Degradation in Teleost Fish

Abstract: NF-κB signaling is tightly regulated and essential to innate and adaptive immune responses, its regulatory mechanism remains unclear in various organisms, especially teleosts. In this study, we reported that IRF3 can negatively regulate TRIF-mediated NF-κB signaling pathway. Overexpression of IRF3 can inhibit TRIF-mediated NF-κB signaling pathway. However, knockdown of IRF3 had an opposite effect. IRF3 can promote the degradation of TRIF protein in mammal and fish cells, but this effect could be inhibited by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…EPC and HEK293 cells were transfected with various plasmids using Lipofectamine 3000 TM (Invitrogen). In addition, proteasome inhibitor MG132 (sigma) or cycloheximide (CHX) (Beyotime) was added into the medium at 24 h post transfection and used at a final concentration of 30 µM/ml and 100 µg/ml (29).…”
Section: Cell Culture and Transient Transfectionsmentioning
confidence: 99%
“…EPC and HEK293 cells were transfected with various plasmids using Lipofectamine 3000 TM (Invitrogen). In addition, proteasome inhibitor MG132 (sigma) or cycloheximide (CHX) (Beyotime) was added into the medium at 24 h post transfection and used at a final concentration of 30 µM/ml and 100 µg/ml (29).…”
Section: Cell Culture and Transient Transfectionsmentioning
confidence: 99%
“…For example, LPS-induced NF-κB activation and TNF production were inhibited by recombinant sTLR4 expressed by macrophages in vitro . In addition, recent investigation in cells of mammals and fish demonstrated that IRF3 negatively regulates the TLR-mediated NF-κB signaling pathway by targeting TRIF for ubiquitination and degradation (32). In brief, hosts initiate robust activation of the innate immune system to guard against pathogens, including LPS, and mobilize a variety of extracellular and intracellular negative feedback pathways to avoid an overstimulated inflammatory state.…”
Section: Role Of Mir-146a In the Toll-like Receptor 4 (Tlr4) Signalinmentioning
confidence: 99%
“…In addition to the regulators that can regulate TRIF in mammals, Zhao et al has recently found a class of regulatory factors that can negatively regulate the TRIF-mediated NF-kB signaling pathway in teleost. They have found that interferon regulatory factor 3 (IRF3) and IRF9 can serve as negative regulators of TRIF to regulate its mediated immune response and prevent the excessive immune response of the body [ 19 , 20 ]. Despite considerable research on mammalian TRIF in antiviral immunity and anti-tumor, research on TRIF in lower vertebrates still has many challenges; therefore, exploration of the regulatory mechanism of TRIF-mediated signal transduction is urgently needed.…”
Section: Introductionmentioning
confidence: 99%